(untitled) - Melvin Merken (Fort Worth, 1993)
The book presents a broad overview of the scientific enterprise. Chapter 2 lays the groundwork for the quantitative aspects of the course, talking up measurement; standardization; the development of the metric system; SI units; multiples and submultiples; exponential notation; and dimentional analysis
Keywords: physical sciences